Risk factors for acute kidney injury in postoperative cardiac surgery (Research, Society and Development, 2021)
Objective: To evaluate the perioperative risk factors associated with postoperative AKI in patients undergoing cardiac surgery. Methodology: Between January 2011 and December 2017, we analyzed prospectively 544 patients, who were divided into two groups: patients with acute kidney injury associated with cardiac surgery (AKI-ACS) defined as an increase of 0.3 mg/dL or 1.5 times the baseline serum creatinine value and control group formed by patients without AKI-ACS. We compared patients and surgical variables using the chi-square test, Fisher's exact test, and mann-Whitney test and logistic regression. Results: AKI-ACS occurred in 29.8% of the patients. In the univariate analysis, the following variables presented a statistically significant difference: male gender (p=0.0087), age (p